Pengaruh Content Marketing dan Fear of Missing Out (FOMO) Terhadap Keputusan Pembelian Mahasiswa Karanganyar Pada E-Commerce Shopee - Yusak Prakoso; Zety Dwiyana (Jurnal Studi Manajemen Bisnis, 2026)
This research aims to explain the effect of content marketing and fear of missing out (FoMO) on the purchasing decisions of students in Karanganyar Regency on the e-commerce platform Shopee. The research method used is quantitative, with a population consisting of 1,170 students in Karanganyar Regency. The study sample comprised 180 respondents, selected through random sampling, in which each individual in the population has an equal chance of being selected. Statistical analysis was conducted in SPSS 27 to test the hypothesis. The results of the research are partial and simultaneous, showing that content marketing and fear of missing out have a significant effect on purchasing decisions. Based on the results of the analysis carried out, the coefficient of determination (R-Square) is 0.565.